Some ultrastructural superficial changes in house fly (Diptera: Muscidae) and blow fly (Diptera: Calliphoridae) larvae induced by eucalyptol oil - Sukontason, Kabkaew L.; Sukontason, Kom; Boonchu, Noppawan; Piangjai, Somsak (Revista do Instituto de Medicina Tropical de São Paulo, 2004)
The ultrastructural superficial changes in third instar house fly (Musca domestica) and blow fly (Chrysomya megacephala) induced by eucalyptol oil were observed using scanning electron microscopy. Dipped in 0.902 g/ml eucalyptol for 30 sec, the larvae integument of both species showed significant aberrant appearance of the body surface, particularly swelling integument, bleb formation, partial breach and deformation of spines.